Determinantes do aleitamento materno exclusivo em uma coorte de nascimento no Espírito Santo - Silva, Ananda Larisse Bezerra da (2023)
Introduction: Exclusive breastfeeding (EBF) is recommended until six months of age and complemented until two years or more, with a healthy diet. There are several benefits of EBF, both for mothers and newborns, however, exclusive breastfeeding rates are below those recommended by the World Health Organization (WHO). Furthermore, there are numerous determinants and factors that can influence adequate breastfeeding practices. Objective: Analyze the determinants associated with exclusive breastfeeding. Methods: The construction of this thesis consisted of three scientific articles, being a scope-type literature review study, which followed the methodology Joanna Briggs Institute (JBI), concomitantly with the recommendations of the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA-ScR) Checklist”, across-sectional, multicenter and quantitative study and another longitudinal, multicenter and quantitative study. For these studies, data from a larger study was used, collected in three maternity hospitals in the State of Espírito Santo. Results: In article 1, 3,998 titles were found and, after all selection steps, 145 studies were included. The health determinants associated with exclusive breastfeeding were mapped: maternal education, family income, attendance and number of prenatal consultations, breastfeeding guidance and practices, time until the first breastfeed, sex of the newborn, maternal work and maternity leave, use of pacifiers and guidance on exclusive breastfeeding in health services. In article 2, exclusive breastfeeding before hospital discharge was 85.2%. Using logistic regression, women under 19 years of age and babies born with normal weight and full-term were more likely to practice exclusive breastfeeding while still in the maternity ward. In article 3, 80.7% remained on EBF on the 7th day and 79.2%onthe27thday after birth. The determinants of EBF on the 7th day after birth were having a partner, consumption of alcohol and/or tobacco, non-use of illicit drugs and normal birth weight. On the 27th day after birth, being up to 19 years of age and being born at term were considered determining factors. Not having difficulties breastfeeding was present in both moments. Final considerations: This thesis proposed to present three articles referring to the theme of determinants associated with exclusive breastfeeding. These studies can contribute to the planning and updating of public policies in favor of breastfeeding, as well as contributing to better results in breastfeeding rates and exclusive breastfeeding.